A Potential Link Between Oral Microbiota and Female Reproductive Health - Justyna Marcickiewicz; Małgorzata Jamka; Jarosław Walkowiak (Microorganisms)
Oral cavity dysbiosis is associated with numerous inflammatory diseases, including diabetes, inflammatory bowel diseases, and periodontal disease. Changes in the oral microenvironment lead to bidirectional interactions between pathogens and individual host systems, which may induce systemic inflammation. There is increasing evidence linking the condition of the oral cavity with the most common causes of female infertility, such as polycystic ovary syndrome and endometriosis, as well as gestational complications, e.g., low birth weight, preterm delivery, and miscarriages. This review highlights the composition of the female oral microbiome in relation to infertility-related disorders, such as endometriosis and polycystic ovary syndrome, and provides a comprehensive overview of the current state of knowledge on the relationship between a dysbiotic oral microbiome, pregnancy, and its impact on the female reproductive tract.